"You too, Second Screeners?" Second Screeners' Echo Chambers During the 2016 U.S. Elections Primaries. Issue 2 (3rd April 2017) - Hayat, Tsahi; Samuel-Azran, Tal
Abstract : This article examines second screeners' conversations during the 2016 U.S. election primaries. Over a 2-week period, we collected Twitter mentions of 3 top cable news shows (N = 49, 568) posted while these shows were broadcast. Using social network analysis, we reconstructed the social network of second screeners (N = 27, 811) and found that the network exhibits ideological homophily with few cross-camp interactions. Our findings strongly indicate the existence of echo chambers in the second screen realm, with more confined echo chambers identified in networks of Twitter followers in comparison to second screeners. The study provides one of the most comprehensive mappings of the second screening phenomenon during an election campaign to date.